(untitled) (International Journal of Engineering and Computer Science, 2014)
Mobile Ad-hoc Networks are formed by nodes which can move dynamically without any controlling stations. These are communication networks in which every node can send and receive data within the network. After the deployment of network the next step is to find a path from source to destination. Routing protocols are used for the path discovery. Broadcasting of data is the primary way to establish a path in MANET. But it has problems like collision and contention. In order to reduce the overloading of the network the route discovery process has to be modified. This work proposes a new method to find the route in an ad-hoc network. The protocol selected for modification is Ad-hoc On-demand Distance Vector. In AODV the route is selected only when there is a requirement for a node to send data to another. In the proposed method route selection is done by the neighbor knowledge which is used to reduce the route overhead in the network. This method is based on a rebroadcast delay and rebroadcast probability. Simulation result shows that this approach can improve the average performance of broadcasting in various network scenarios. This method is simple and can be easily implemented in MANET.